An application detector system for computer security purpose - Kamaruldzaman, Mohamed (Universiti Malaysia Sarawak, (UNIMAS), 2003)
"An Application Detector System for Computer Security Purpose" is a detector system that combines hardware and software. The main purpose of this project is to develop an efficient and cheap detector system in order to solve the computer stolen problem in computer laboratory without the increase in workforce. Any unauthorized removal of the computer will detected by sensor circuit. The sensor circuit will send the signal to the authorized user through parallel port. The Graphical User Interface (GUI) which is written using Microsoft Visual C++ will specify which computer is being removed and will trigger the signal to activate the alarm. Hopefully the detector system will increase the efficiency and effectiveness of security level in computer laboratory of University Malaysia Sarawak (UNIMAS).